A review on disinfection methods for inactivation of waterborne viruses - Lanrewaju, Adedayo Ayodeji; Enitan-Folami, Abimbola Motunrayo; Sabiu, Saheed; Swalaha, Feroz Mahomed (Frontiers in Microbiology, 2022)
Water contamination is a global health problem, and the need for safe water is ever-growing due to the public health implications of unsafe water. Contaminated water could contain pathogenic bacteria, protozoa, and viruses that are implicated in several debilitating human diseases. The prevalence and survival of waterborne viruses differ from bacteria and other waterborne microorganisms. In addition, viruses are responsible for more severe waterborne diseases such as gastroenteritis, myocarditis, and encephalitis among others, hence the need for dedicated attention to viral inactivation. Disinfection is vital to water treatment because it removes pathogens, including viruses. The commonly used methods and techniques of disinfection for viral inactivation in water comprise physical disinfection such as membrane filtration, ultraviolet (UV) irradiation, and conventional chemical processes such as chlorine, monochloramine, chlorine dioxide, and ozone among others. However, the production of disinfection by-products (DBPs) that accompanies chemical methods of disinfection is an issue of great concern due to the increase in the risks of harm to humans, for example, the development of cancer of the bladder and adverse reproductive outcomes. Therefore, this review examines the conventional disinfection approaches alongside emerging disinfection technologies, such as photocatalytic disinfection, cavitation, and electrochemical disinfection. Moreover, the merits, limitations, and log reduction values (LRVs) of the different disinfection methods discussed were compared concerning virus removal efficiency. Future research needs to merge single disinfection techniques into one to achieve improved viral disinfection, and the development of medicinal plant-based materials as disinfectants due to their antimicrobial and safety benefits to avoid toxicity is also highlighted.